AB0225 Clinical outcomes of treatment with golimumab in seropositive and seronegative rheumatoid arthritis patients in real-life settings. data from italian register gisea. (12th June 2018) - Iannone, F.; Caporali, R.; Grosso, V.; Favalli, E.G.; Marchesoni, A.; D'Angelo, S.; Tramontano, G.; Sarzi-Puttini, P.; Atzeni, F.; Conti, F.; Miranda, F.; Foti, R.; et al.
Abstract : Background: There is evidence that autoimmunity, namely RF and ACPA antibodies, may influence disease activities and impact the clinical outcomes in RA. Objectives: There is evidence that autoimmunity, namely RF and ACPA antibodies, may influence disease activities and impact the clinical outcomes in RA. Methods: We analysed longitudinal data of consecutive RA patients from the Italian registry GISEA, starting a treatment with golimumab (GOL) and tested for rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA). Demographic and disease related characteristics were collected at baseline, 6 months, 12, and 24 months or at last observation visit. Primary endpoint was the persistence on GOL in RF/ACPA +ve and RF/ACPA patients. Secondary endpoint was the search of baseline predictors of drug survival and clinical outcomes n the two RA subsets. Drug survival was evaluated by Kaplan-Meier life table analysis. Estimates hazard ratios (HRs, 95% confidence intervals (CI)) of drug discontinuation or achievement of low-disease adjusted for patient's demographics, disease characteristics and prior biologic treatments were computed by Cox-regression stepwise backward models. Results: 345 patients had data on RA and ACP testing and were included in this analysis. No significant difference in terms of age, BMI, disease activity, co-therapy with glucocorticoids or methotrexate (MTX) was detected between RF/ACPA+ve and RF/ACPA-ve patients, but the former had significantly higher disease duration (10.6±vs 8.2±6 years) and frequencies of comorbidities (60.6% vs 44.2%). The 2 years global drug retention was 64.5%, and it was almost identical in RF/ACPA+ve 64.2% and in RF/ACPA-ve 65% RA patients. Drug survival was not influenced by the gender or cause of discontinuation (adverse or inefficacy). To note, in 31% of the patients GOL was not associated to MTX. The only predictor of drug discontinuation was the lack of MTX at baseline (HR 1.62, 95 CI 1.07–2.46, p=0.02), and the GOL-naïve status (HR 0.62, 95 CI 0.39–0.99, p=0.04). At two years, 44.4% achieved the state of low-disease activity (DAS28 <3.2) with no difference between RF/ACPA+ve (45.4%) and RF/ACPA-ve (42.0%) patients, and none baseline factor correlating with low disease activity. No safety issues were raised during the study. Conclusions: In this study, we demonstrated that RF/ACPA positivity does not negatively impact on drug survival on golimumab. This may aid rheumatologists in their clinical decisions. Disclosure of Interest: None declared